Genetic diversity of Castanopsis eyrei populations in three forest communities with different succession stage - LI Jun-min; JIN Ze-xin (浙江大学学报. 农业与生命科学版)
RAPD (Random amplified polymorphic DNA) was used to detect the genetic diversity of Castanopsis eyrei populations in three forest communities at different succession stages in Tiantai mountain Zhejiang Province, namely, needle-leaved forest, needle/broad-leaved mixed forest and evergreen broad-leaved forest. The total percentage of polymorphic loci of Castanopsis eyrei was 92.13% with an average of 67.98%. The highest genetic diversity as estimated by Shannon index was shown to exist in evergreen broad-leaved forest community with a 0.4188 average index. Next in degree of diversity was the needle/broad-leaved mixed forest community, and the average index of which was 0.3873. The last genetic diversity was shown to exist in needle-leaved forest community with an average of 0.3613. Of the total genetic diversity, 75% was ascribed to the differentiation among populations while 54.41% resided within populations. Judged from the so-called Nei's index, however, genetic diversity of evergreen board-leaved forest community ranked first and was 0.2858, followed by needle, broad-leaved mixed forest community (0.2642) and, then, needle-leaved forest community (0.2434). The coefficient of gene differentiation (Gst) was 0.2473 and the gene flow estimated from Gst was only 1.5542. Genetic distances as defined by Nei between every two populations were also calculated, which ranged from 0.1757 to 0.2134. The clustering analysis showed that the evergreen broad-leaved forest community gathered initially with the needle/broad-leaved mixed forest community, and later with the needle-leaved forest community.